Perempuan Post-Menopause dengan Pseudocyesis di Daerah Rural : Segi Perspektif Sosial Budaya - I Made Wikrama Resindra; Jessica Gloria Mogi; Rivo Mario Warouw Lintuuran (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2024)
Introduction: Pseudocyesis originates from the Greek language, consisting of 2 syllables, namely: Pseudo (false) and Kyesis (pregnancy). Pseudocyesis is a mental health condition where the affected individual believes they are pregnant, accompanied by signs and symptoms of pregnancy. The Kei society adheres to a patrilineal kinship system and has preserved customary laws handed down through generations known as “Larvul Ngabal”. These customary laws regulate several aspects of life including marriage and descent.Case Report: A 60-year-old woman came to the outpatient clinic to checked her pregnancy. The patient stated that for the past 2 months, her abdomen had been growing larger and she felt fetal movements inside. Obstetric examination and supporting tests did not reveal the presence of a fetus. The patient was educated that she was not pregnant, but she remained convinced that she was pregnant.Case Discussion: This patient has already entered post-menopausal age and has been married for the second time. The patient and her husband desire to have a male child. The Kei society adheres to a patrilineal system, where a male child is hoped to continue or strengthen the paternal lineage. However, the patient currently does not have any offspring. Therefore, this situation may have an impact on her condition.Conclusion: Pseudocyesis reflects somatization disorder in the patient due to the unfulfilled desire to have offspring. This condition can be influenced by several factors including socio-cultural ones.